Deformation analysis of foundation: a case study from the Bir Hospital Trauma Centre, Kathmandu, Nepal - Adhikari, AR; Pradhan, AMS (Journal of Nepal Geological Society, 2008)
The rapid increase in population of Kathmandu valley in last two decades has demanded the construction of multistoried buildings. Statistical analysis shows that the deformation after the construction of structures are rarely considered during the design phase of the structure which can be vulnerable to the structure itself. The excessive settlement of the foundation causes the failure of the foundation and ultimately the building causing the huge amount of lives and property loss. The failure process is more pronounced when the foundation is placed in soft fluviolacustrine sediments of Kathmandu valley. Therefore, this paper aims in estimating the settlements and deformation after construction of structure by manual and Finite Element Methods. The subsurface stratification, their geotechnical properties; size and shape of foundation and that of building were considered for deformation analysis of foundation. The geotechnical properties are found in the laboratory and few are estimated by graphical methods. The deformation analysis of the foundation should be considered in two aspects i.e. bearing capacity failure and settlement. Settlement calculated by conventional test methods i.e.oedometre test, compressibility index are purely one-dimensional and doesn’t represent the actual value where lateral influences are possible. The settlement by conventional methods is 41.6 mm for stratification below 4 m depth and 24 mm for stratification below 8 m depth. Whereas, using finite element method, it is 42 mm for stratification below 8m depth using same parameters valid for the site and considering the horizontal displacement. The stress distribution and depth of foundation favors the foundation. Journal of Nepal Geological Society, 2007, Vol. 36 (Sp. Issue) p.18